Recent development in triboelectric nanogenerators: a review - Emaediong Sylvanus Udofa (23770923) (2025)
Triboelectric nanogenerators (TENGs) are rapidly emerging as a pivotal technology for sustainable energy harvesting and sensing. This review offers a structured analysis that spans theoretical foundations, with detailed comparison of existing models with performance metrics, and operational modes, while critically examining material selection, combination strategies and their influence on charge density. Environmental factors such as humidity and temperature are evaluated for their impact on efficiency, and surface modification techniques are reviewed to highlight performance enhancement pathways. Applications across biomedical, autonomous vehicle, agricultural, marine, power infrastructure, smart city sectors, textiles, human machine interface and electronic skin are synthesized, leading to a developmental roadmap that connects current progress with future prospects. Despite rapid advancements, the large-scale adoption of TENGs remains constrained by low output current, material degradation, power management and miniaturization challenges. Addressing these issues requires integrative strategies: interface and surface engineering with advanced semiconductors, two-dimensional materials, MXene, nano-structured, and metal–organic framework to boost charge density and current stability. In addition, protective coatings and robust composites are essential to enhance durability, while circuit optimizations and hybrid designs with scalable fabrication techniques enable efficient miniaturization. By uniting these innovations, TENGs are poised to transition from laboratory-scale prototypes to practical technologies, positioning them as a cornerstone of next-generation autonomous electronics and sustainable energy ecosystems. Other Information Published in: Journal of Materials Science: Materials in Electronics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10854-025-16223-7